Generalization of Hilbert-Hardy Integral Inequalities - Mahrouf, Sobhy a (Kuwait Journal of Science, 2018)
In this paper, Hilbert's integral inequalities with some parameters are considered, by using new methods in the proof. Several results of Hardy and Yang are special cases of the new given inequality. As an application, we give some applied examples that illustrate our results.